Stability of biochar and its influence on the dynamics of soil properties : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Soil Science, Institute of Natural Resources, College of Sciences, Massey University, Palmerston North, New Zealand - Herath, Herath Mudiyanselage Saman Kumara (Massey University, 2012)
The overall objective of this PhD was to investigate the stability of specific biochars – produced from corn stover (Zea mays L.) at 350 °C (CS-350) and 550 °C (CS-550) – and their roles on the dynamics of native organic matter (NOM) and physical properties of a Typic Fragiaqualf (Tokomaru soil; TK soil) and a Typic Hapludand (Egmont soil; EG soil). Except for the controls, all other treatments received a 7.18 t C ha–1 application, either as fresh corn stover or as biochar. After 295 d, bulk density, saturated hydraulic conductivity (Ks), volumetric moisture content (θV), aggregate stability and soil water repellency were measured. At that sampling time, two undisturbed subsamples from each pot were taken: (i) in one subsample, lucerne (Medicago sativa L.) was seeded; (ii) in the other, the incubation was continued without plants. All pots were additionally incubated for 215 d. During the 510 d incubation, the CO2-C efflux rate was determined for the selected 82 d, and samples for 19 d out of these 82 d were analysed for δ13CO2. Soil samples at T0, T295 and T510 (with and without plants) were physically fractionated into coarse and fine free particulate organic matter (fPOM), silt+clay, and heavy fraction (HF), and analysed for δ13C and total OC. Dichromate oxidation and acid hydrolysis were also conducted for the bulk soil and physical fractions. Biochar application significantly increased (P<0.05) the aggregate stability of both soils (the effect of CS-550 biochar being more prominent in the TK soil than that in the EG soil, and the reverse pattern being observed for the CS-350 biochar), and the volumetric moisture content (θV). The latter effect was generally more evident in the TK soil than that in the EG soil, at both T0 and T295. Biochar addition significantly (P<0.05) increased the macroporosity in the TK soil and also the mesoporosity in the EG soil. Biochar also significantly increased (P<0.05) Ks of the TK soil but not that of the EG soil. However, biochar was not found to increase water repellency of these soils. Overall, the results suggest that these biochars may facilitate drainage in the poorly drained TK soil and potentially reduce N 2O emissions. Total accumulated CO2-C evolved from the corn stover treatment was significantly higher (P<0.05) than that from rest of the treatments. No significant differences (P<0.05) were observed in the rate of CO2-C evolution between the controls and biochar treatments. In both soils, fresh corn stover had a net positive priming effect on the NOM decomposition, while biochar had a net negative priming effect in the TK soil, but no effect in the EG soil. When a C balance was made considering the C lost during pyrolysis, the combination of CS-350 biochar and EG soil provided the greatest C saving of all treatments. When the different priming effects on NOM were also considered, differences among the two soils were balanced. The longer half-life (494 y) corresponded to the CS-550 biochar in the TK soil, while the half-lives of the other biochar-soil combinations were <200 y. It was estimated that 55 – 70 % of amended biochar-C would remain in soil after 100 y. After 295 d, >78 % of biochar-C recovered in the TK soil and >64 % of biochar C in the EG soil ended in the coarse fPOM, >13 % (TK) and >21 % (EG) in the fine fPOM fraction, and the rest in the silt+clay fraction. The same pattern was observed after 510 d, both with and without plants. Most of the biochar particles thus concentrated into the “unprotected pool”. The use of dichromate oxidation to distinguish the recalcitrant fraction of C in the “unprotected pool” is suggested. Finally, the presence of both biochar and plants induced an additional accumulation of total organic carbon (OC) in the TK-350 and EG-550 soils (P<0.05), compared with the treatments with plants but no biochar. The use of biochars in these OC-rich soils was proven to be adequate to promote C sequestration, especially when compared to the direct application of the fresh feedstock. This enhanced C sequestration is suggested to occur through (i) the addition of a stable C source (e.g., condensed aromatic C in biochar), (ii) the protection of NOM (especially in the TK soil), and (iii) the interaction of biochar with new OC inputs to soil (e.g., root exudates). The results from this study also indicated that long-term incubations in the absence of a continuous fresh input of plant material may create artefacts such as reduced aggregate protection and an apparent loss of aggregate protected OC. Future research should be directed to investigate (i) the influence of these physicochemical changes on microbial activity, population and diversity; and (ii) the evolution of these interactions under field conditions.
Keywords: Biochar; Soil properties; Soil stability; Carbon sequestration